Differential Interleukin-10 and Gamma Interferon mRNA Expression in Lungs of Cilium-Associated Respiratory Bacillus-Infected Mice - Kendall, Lon V. (American Society for Microbiology, 2001)
The cilium-associated respiratory (CAR) bacillus is a gram-negative, extracellular bacterium that causes persistent respiratory tract infections in rodents. We have previously demonstrated that BALB/c mice are more susceptible to CAR bacillus-induced disease than resistant C57BL/6 mice, with elevations in pulmonary gamma interferon (IFN-γ) and interleukin (IL)-4. IL-10 is a type 2 cytokine that can increase host susceptibility to bacterial diseases through its anti-inflammatory effects, including suppression of macrophage function. The purpose of this study was to further describe the cytokine profiles associated with histologic lesions in CAR bacillus-infected mice and to assess the effects of cytokine depletion on the pathogenesis of disease. Six-week-old female BALB/c and C57BL/6 mice and mice with targeted mutations in IFN-γ and IL-4 were inoculated intratracheally with 10(5) CAR bacillus organisms, and samples were collected at 6 to 7 weeks postinoculation. Lung samples were collected for histopathologic examination and analysis of cytokine mRNA. IFN-γ, IL-10, and IL-4 mRNA levels in the lungs of infected mice were semiquantitatively measured using a reverse transcriptase-mediated PCR assay and compared to those in uninfected control animals of each strain. BALB/c mice infected with CAR bacillus had a median lung lesion score of 6 and IL-10 and IL-4 mRNA levels were significantly elevated. The majority of C57BL/6 mice were resistant to disease characterized by lung lesions scores of 2 or less and a dominant IFN-γ mRNA cytokine profile. A few C57BL/6 mice with lesions scores of 5 or greater had elevations in all three cytokines and were susceptible to disease. C57BL/6 IFN-γ knockout mice had increased disease with elevations in IL-10 and IL-4 mRNA, while BALB/c IL-4 knockout mice infected with CAR bacillus had a mild decrease in lesion severity and an attenuated IL-10 mRNA expression compared to wild-type BALB/c mice. These data indicate that IL-10 and IL-4 predominate in CAR bacillus-induced histologic lesions in mice, while IFN-γ may play a role in resistance to disease.